2018
DOI: 10.1002/jsfa.9309
|View full text |Cite
|
Sign up to set email alerts
|

Leaf removal at veraison stage differentially affects qualitative attributes and bioactive composition of fresh and dehydrated grapes of two indigenous Cypriot cultivars

Abstract: Leaf removal at veraison stage followed by sun drying differentially affected the chemical composition of the examined cultivars. This preharvest application followed by postharvest dehydration was beneficial for cv. 'Mavro', while this was not the case for cv. 'Xynisteri'. The effects of leaf removal in other developmental stages (i.e. pre/post bloom stage) need to be dissected with the ultimate goal of providing an end product with high bioactive content. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In summary this was the first detailed sensory, chemical and consumer study of wines made from the indigenous Cypriot grape varieties Xynisteri, Maratheftiko and Giannoudhi. This work has built on previous work from other authors (Constantinou et al, 2017;Constantinou et al, 2018a;Constantinou et al, 2018b;Galanakis et al, 2015;Kokkinofta et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In summary this was the first detailed sensory, chemical and consumer study of wines made from the indigenous Cypriot grape varieties Xynisteri, Maratheftiko and Giannoudhi. This work has built on previous work from other authors (Constantinou et al, 2017;Constantinou et al, 2018a;Constantinou et al, 2018b;Galanakis et al, 2015;Kokkinofta et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…To date there is limited research on sensory and chemical profiling of wines made from Cypriot grape varieties. Research has mainly focused on investigating the chemical composition and metabolic fingerprints of sun dried Xynisteri grape musts (Constantinou et al, 2017;Constantinou et al, 2018a), the phenolic content and antioxidant capacity of Cypriot wines (Galanakis et al, 2015) and the authenticity of Cypriot wines using isotopic markers (Kokkinofta et al, 2006 and2017).…”
Section: Introductionmentioning
confidence: 99%
“…During grape dehydration, researchers observed the modification of the cell wall composition and, consequently, the alteration of the permeability of the membranes, improving the extractability of some components [79,86]. Wines obtained starting from post-harvest dehydrated grapes showed higher content of phenols than the analogous wines obtained from fresh grape [61,[87][88][89]. Therefore, the contribution to the rise of these molecules is not only directly dependent on their level in the processed berries, but it is probably also linked to the degradation of internal skin cell layers occurring under dehydration, which can enhance phenol and anthocyanin extractability [60,71].…”
Section: Quality Of Wine From Postharvest Dehydrated Grapementioning
confidence: 99%
“…Less time was needed for ND samples; at 10 C, the dehydration time was between 27 (ND) and 32 (DFS) days, and samples lost mass similarly to those dehydrated at 20 C. After 10% ML, different trends were observed depending on the dehydration temperature: the ND, DFS and DPV samples dehydrated over different times at 10 C, but not at 20 C. To date, few published papers have reported the grape dehydration response following defoliation of grapevines. Constantinou et al (2019) reported the effect of leaf removal at veraison on grape composition, but for sun-dried grapes, which is a different process, compared to dehydration of grapes under controlled ambient conditions. In the current study, the controlled conditions enabled accurate measurement of the time of dehydration.…”
Section: Resultsmentioning
confidence: 99%